Education and training for organic types of agriculture: an outline of demands and a conceptual framework - Mansalvet, J.D. Van
Sumario (En)
Ilus.; 40 ref.
Keywords: CAPACITACION; AGRICULTURA ORGANICA; DESARROLLO ECONOMICO Y SOCIAL